Effect of metabolic syndrome on coronary heart disease in rural minorities of Xinjiang: a retrospective cohort study - Changjing Li; Jia He; Bin Wei; Xianghui Zhang; Xinping Wang; Jingyu Zhang; Kui Wang; Yunhua Hu; Lati Mu; Yizhong Yan; Jiaolong Ma; Yanpeng Song; et al. (BMC, 2020)
Abstract Background Metabolic syndrome is diagnosed by a cluster of risk factors that associated with an increased risk of coronary heart disease (CHD). We aimed to explore the impact of and interactions between individual metabolic syndrome components on the risk of CHD in Xinjiang. Methods The baseline population included 7635 participants. The degree to which the components increase the risk of CHD and the multiplicative interactions between them were assessed using hazard ratios (HRs) and 95% confidence intervals (CIs). Additive interactions were appraised by the relative excess risk due to interaction, synergy index (SI), and attributable proportion of interaction. Results A total of 304 CHD patients were enrolled from rural residents of Xinjiang. Elevated blood pressure (HR 1.81; 95% CI 1.35-2.44) and elevated fasting blood glucose (FBG) (HR 1.82; 95% CI 1.38-2.38) increased the risk of CHD after adjustment for confounding factors. We found a positive additive interaction (SI 1.14; 95% CI 0.51-2.51) between elevated blood pressure and elevated FBG, but none were significant. As the number of components increased, the risk of CHD increased. The combinations of [high triglycerides (TG) + low high-density lipoprotein cholesterol (HDL-C) + elevated FBG + large waistline] (HR 4.26; 95% CI 1.43-12.73) and [elevated blood pressure + elevated FBG + low HDL-C + large waistline] (HR 1.82; 95% CI 1.38-2.38) increased the risk of CHD. Conclusions We provide evidence that elevated blood pressure and elevated FBG are independent risk factors for CHD and it might be necessary to maintain the normal waistline for preventing CHD.